Eliminación simultánea de amonio y 2-clorofenol: análisis cinético y molecular - Martínez Jardínes, Miguel Ángel (Universidad Autónoma Metropolitana, 2020)
Simultaneous ammonium and 2-chlorophenol (2-CP) consumption by a nitrifying sludge was evaluated in two SBR reactors fed with 60 mg 2-CP-C/L and different initial concentrations of ammonium. The physiological, kinetic and molecular analysis was carried out, as well as their possible relationship through 13 operating cycles: one with 100, three with 200, three with 300, three with 400 and three cycles with 500 mg NH4 + -N/L. The physiological behavior of the sludge was assessed using the ammonium (ENH4 + -N) and 2-CF (E2-CP-C) consumption efficiencies and the nitrate production yield (YNO3 - -N) whereas the kinetic behavior was evaluated by the specific rates of ammonium (qNH4 + -N) and 2-CF (q2-CP-C) consumption and nitrate generation (qNO3 - -N). The molecular and population dynamic analysis of the nitrifying sludge were determined by means a DGGE of the DNA of bacteria at the end of each operation cycle. An ecological index of species richness (S) and evenness (J) were calculated. Likewise, the most representative DGGE bands were sequenced. Finally, different correlations were conducted between the nitrifying behavior and the molecular response. Throughout the operation cycles and regardless to the increase in the ammonium concentration, the sludge presented a complete nitrification in 14 days of culture, obtaining ENH4 + -N close to 99% and YNO3 - -N between 0.93 and 0.99 g NO3 - -N/g NH4 + -N consumed. Likewise, the sludge was able to fully consume the 2-CP in 7 days with E2-CP-C of 100%. The increase in the ammonium concentration throughout the operating cycles provoked in cycle 13 of operation a respectively increase in qNH4 + -N, qNO3 - -N and q2-CP-C (values of 189.3, 148.9 and 69.1 mg/g of protein d in cycle 13 respectively) of up to 5.1, 5.2 and 3.1 times regarding to cycle 1. A direct and significant relationship between the qNH4 + -N and q2-CP-C with a correlation coefficient of 0.83 was determined, showing effect of the increase in ammonium concentration on the cometabolic 2-CP consumption. Batch assays conducted with the sludge inoculated into the reactors in presence of allylthiourea as specific inhibitor of the ammonium monooxygenase enzyme (AMO), resulted in a decrease of 34.2±4.7% in q2-CP-C, evidenced the participation of the AMO in the consumption of 2-CP.; El consumo simultáneo de amonio y 2-clorofenol (2-CF) por un lodo nitrificante se evaluó en dos reactores SBR alimentados con 60 mg C-2-CF/L y diferentes concentraciones iniciales de amonio. Se llevó a cabo el análisis fisiológico, cinético y molecular, así como su posible relación a través de 13 ciclos de operación: un ciclo con 100, tres ciclos con 200, tres ciclos con 300, tres ciclos con 400 y tres ciclos con 500 mg N-NH4 + /L. El comportamiento fisiológico y cinético de los lodos se evaluó mediante la eficiencia de consumo de amonio (ENNH4 + ) y 2-CF (EC-2-CF), el rendimiento de producción de nitrato (YN-NO3 - ) y las velocidades específicas de consumo de amonio (qN-NH4 + ) y 2-CF (qC-2-CF) y producción de nitrato (qNNO3 - ). La dinámica poblacional y el análisis molecular del lodo nitrificante se determinó mediante un DGGE del ADN de bacterias al final de cada ciclo de operación. Se calcularon los índices ecológicos de riqueza de especies (S) y equitatividad (J), también se secuenciaron las bandas más representativas del DGGE. Por último, se llevaron a cabo diferentes correlaciones entre las variables de respuesta fisiológicas y cinéticas nitrificantes con la respuesta molecular. A lo largo de los ciclos de operación e independientemente del aumento en la concentración de amonio, el lodo presentó una nitrificación completa en 14 días de cultivo, obteniéndose ENNH4 + cercanas al 99% y YN-NO3 - entre 0.93 y 0.99 g N-NO3 - /g N-NH4 + consumido. Asimismo, el lodo fue capaz de consumir completamente el 2-CF en 7 días con EC-2-CF del 100%. El aumento en la concentración de amonio a lo largo de los ciclos provocó un incremento en las qN-NH4 + , qN-NO3 - y qC-2-CF (valores de 189.3, 148.9 y 69.1 mg/g de proteína d en el ciclo 13 respectivamente) de hasta 5.1, 5.2 y 3.1 veces respectivamente en el ciclo 13 de operación con respecto al ciclo 1. Se determinó que existe una relación directa y significativa entre las qNNH4 + y qC-2-CF con un coeficiente de correlación de 0.83 entre ambas velocidades, mostrando el consumo cometabólico de 2-CF. En ensayos en lote utilizando aliltiourea como inhibidor específico de la enzima amonio monooxigenasa (AMO), se encontró que, con el lodo inoculado a los reactores, la qC-2-CF disminuyó 34.2±4.7%, mostrando la participación de la AMO en el consumo del 2-CF. ; Cuando se realizó la misma prueba con el lodo proveniente de los reactores SBR después de 13 ciclos de operación, se observó una mayor participación de la actividad amonio oxidante con una disminución del 52.3±7.7% en la qC-2-CF A lo largo de la experimentación y de acuerdo al DGGE, se presentaron cambios en el índice S, con una tendencia a la disminución. Se inició con un índice J de 0.89 y terminó en 0.99. La comunidad bacteriana tuvo una tendencia a la homogeneidad y podría estar asociada a la estabilidad del proceso nitrificante. Las especies encontradas se agruparon como βproteobacteria (45%), acidobacteria (30%), γ-proteobacteria (10%) y deinococcus-thermus (15%). El consumo simultáneo de amonio y 2-CF se podría atribuir a la detección y permanencia de especies de bacterias amonio oxidantes (AOB). La nitrificación completa, se podría atribuir a la presencia de especies de bacterias nitrito oxidantes (NOB) y el consumo de 2-CF a bacterias heterotróficas de los grupos Acidobacteria, γ-proteobacteria y deinococcus-thermus. La disminución en S y la tendencia a la homogeneidad (J = 0.99) se puede asociar con la concentración de amonio y los ciclos de operación (r de -0.56 y -0.61 y de 0.82 y 0.89 respectivamente). Por otro lado, la comunidad homogénea (J) se asocia con la respuesta fisiológica y cinética del proceso nitrificante (r>0.60). Además, la disminución en S y la tendencia a la homogeneidad se asocia con la qC-2-CF, p pero no con la EC-2-CF (r de -0.65 y 0.85; r de -0.45 y 0.28 respectivamente). En el mismo sentido, al relacionar la intensidad de banda de las especies obtenidas del DGGE (interpretada como la proporción de especies presentes) con la respuesta nitrificante, se estableció que el aumento en la proporción de individuos de las diferentes especies obtenidas del DGGE del lodo nitrificante se asocian con la concentración de amonio y los ciclos de operación. Se determinó que el aumento en la proporción de individuos de especies de AOB se asocian con la EN-NH4 + , con el incremento de la qN-NH4 + y qC-2-CF. Se estableció que el aumento en la proporción de individuos de especies heterotróficas se asocia con el incremento de la qC-2-CF. De acuerdo a estos resultados, Al final de la experimentación con 60 mg C-2-CF/L y una concentración de 500 mg de N-NH4 + /L, se obtuvo una comunidad bacteriana homogénea con el aumento en proporción de individuos de algunas especies, que contribuyeron a un proceso fisiológicamente estable con q altas y un consumo cometabólico de 2-CF por la enzima AMO. El uso de sistemas SBR con lodos nitrificantes puede ser una buena alternativa para aumentar el consumo cometabólico de compuestos recalcitrantes como el 2-CF y tratar efluentes contaminados con altas concentraciones de amonio.; When these assays were carried out with the sludge obtained after 13 operating cycles in the SBR reactors, a higher participation of the AMO in 2-CP consumption was noticed with a decrease of 52.3±7.7% in q2-CP-C. According to experimentation, changes in the S index were observed with a decreasing tendency. The bacterial community showed a tendency to homogeneity as an initial J index of 0.89 was calculated whereas a J value of 0.99 was determined at the end of experimentation. This behavior might be associated with the stability of the nitrifying process. The identified species were grouped as β-proteobacteria (45%), acidobacteria (30%), γ-proteobacteria (10%) and deinococcus-thermus (15%). The simultaneous consumption of ammonium and 2-CP could be attributed to the detection and permanence of species of ammonium oxidizing bacteria (AOB). Complete nitrification could be attributed to the presence of a NOB specie and 2-CP consumption to the presence of heterotrophic bacteria of Acidobacteria group, γ-proteobacteria and deinococcus-thermus group. The decrease in S and the tendency to homogeneity (J = 0.99) was associated with the ammonium concentration increase and the operating cycles (r of -0.56 and -0.61 and of 0.82 and 0.89 respectively). On the other hand, homogeneous community (J) was associated with the physiological and kinetic response of the nitrifying process (r>0.60). Furthermore, the decrease in S and the tendency to homogeneity were only associated with q2- CP-C (r of -0.65 and 0.85; r of -0.45 and 0.28 respectively). In the same sense, when relating the band intensity of the species obtained of DGGE (interpreted as the proportion of species present) with the nitrifying response, it was established that the increase in the proportion of individuals of the different species obtained from DGGE of nitrifying sludge was associated with ammonium concentration and operating cycles. It was established that the increase in the proportion of individuals of AOB species were associated with ENH4 + -N values higher than 99%; with the increase in qNH4 + -N and the increase of q2-CP-C. It was established that the increase in the proportion of individuals of heterotrophic species were associated with the increase in q2-CP-C. According to these results, at the end of the experimentation with 60 mg of 2-CP-C/L and 500 mg of NH4 + -N/L, a homogeneous bacterial community was obtained. Under these conditions an increase in proportion of individuals of some species might contribute achieve a physiologically stable nitrifying process with high q and a cometabolic 2-CP consumption enhanced by the AMO enzyme. The use of nitrifying SBR systems could be considered as a suitable alternative for increasing the cometabolic consumption of recalcitrant compounds such as 2-CP besides treating effluents highly contaminated with ammonium.